الخلفية التاريخية لنشأة الديداكتيك قراءة في المفهوم والموضوع - مشطر, حسين (جامعة الوادي - University of Eloued, 2018)
تقوم الديداكتيك على قاعدتين أساسيتين الأولى قاعدة أفقية وتتضمن دراسة الظاهرة التعليمية الممارسة كما تبدو والتي تتجلى من خلال التفاعلات اليومية بين المدرس والتلميذ، والقاعدة الثانية عمودية وتتضمن معرفة الطفل(التلميذ) من حيث عاداته ولغته وأخلاقه التي يحملها من مجتمعه والتي ترافقه إلى الوسط المدرسي وتؤثر على عملية تعلمه أو ما يعرف ب "انثربولوجيا الطفل" بمعني تاريخه الشخصي المرتبط بثقافة الوسط الذي يعيش فيه، يقول المثل الانجليزي "إذا أردت تعليم اللاتينية لجون فأبد بجون أولا ثم اللاتينية". ومن هنا نعرض للتطور التاريخي لمفهوم الديداكتيك مع أهم موضوعاتها ثم نختتم بإسقاطات لممارسات ديداكتيكية في الفعل التعليمي التعلمي.Didactics is based on two basic bases, the first is a horizontal base and includes the study of the educational phenomenon practiced as it appears, which is manifested through the daily interactions between the teacher and the student. His learning process, or what is known as "the child's anthropology," meaning his personal history linked to the culture of the environment in which he lives, the English proverb says, "If you want to teach Latin to John, start with John first, then Latin." Hence, we present the historical development of the concept of didacticism with its most important topics, and then we conclude with projections of didactic practices in the educational-learning act.
The Historical Background of the Emergence of Didactics: A Reading in Concept and Subject
مقال
Keywords: الديداكتيك، التطور التاريخي للديداكتيك، انواع الديداكتيك.; Didactics, Historical development of Didactic; Species of didactic